Desain Instalasi Mandi, Cuci, dan Kakus di Cipapais, Kelurahan Kadumerak, Kabupaten Pandeglang - Fikha Raihani; Yudi Chadirin; Heriansyah Putra; Triyogo Aleksandria; Shahilla Larasaty; Risma Amelia; Giri Rasyidpradana Ganda; Nurul Chairunnisa; Devya Meisnnehr; Fazrina Andriani Sakinah Lubis; Muhammad Adhiragil Kandyas (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Bathrooms and toilets are very much needed by the community. Cipapais is located at the end of Kadumerak Village, Pandeglang Regency which does not yet have good sanitation facilities. Residents around still doing bathing, washing, and toilet facilities in the river. The river used for these activities has been polluted by domestic waste water and garbage. In addition, many residents practice latrines in the irrigation stream. These things can cause disease. The design of MCK installation design is done by calculation according to SNI. The MCK planning procedure is actually standardized and there are three important facilities, bathroom facilities, washing facilities, and latrine facilities. The purpose of this community service activity is the design of the Toilet Washing Toilet (MCK) in Cipapais Village, Kadumerak Village, Karangtanjung District, Pandeglang Prefecture. This research was conducted in July 2019 in Kadumerak Village, Karang Tanjung District, Pandeglang Prefecture.This calculation assumes that the needs of people for MCK are 400 people with an average of 40 liters / person / year of sludge generated and waste water produced is 10 liters / person / day. The capacity for collecting mud is 32,000 liters. The minimum holding time requirement for precipitation is 0.42. The need for holding water capacity is 1,680 m3. The volume of communal septic tanks produced 33.68 m3. From these results, the height, width and length of the septic tank are 2 meters high, 2.9 meters wide and 5.8 meters long. Keywords: MCK, river cleanliness, septic tank design